Successful application of keratinocyte suspension using autologous fibrin spray. Issue 3 (May 2017) - Johnstone, Philippa; Kwei, Johnny Sheng-Sun; Filobbos, George; Lewis, Darren; Jeffery, Steven
Highlights: The back is a challenging anatomical area to resurface in acute burns. The co-delivery of Recell ® suspension with fibrin via Vivostat ® system is proposed. This mechanism increases anchorage of fibrin suspended cells to the wound surface. Shows potential to improve wound healing in acute burns, particularly complex areas. Abstract: Objective: The back is a challenging anatomical area to resurface in acute burns due to its large surface area, its dependent position with the patient lying down and the shearing forces applied to any method of resurfacing employed. This case study presents the use of Vivostat ® (Vivostat A/S, Lillerød, Denmark) in resurfacing the back in conjunction with Recell ® regenerative epithelial suspension. Vivostat ® (Vivostat A/S, Lillerød, Denmark) is a "novel patented biotechnological process that enables reproducible preparation of autologous fibrin sealant or platelet rich fibrin without cryoprecipitation or a separate thrombin component"[1] . Methods: A 29-year-old female sustained 27% total body surface area (TBSA) flame burns, including the whole back. This area was initially grafted with the sandwich autograft/allograft technique on day four after injury, with approximately 80% graft take on day eight. Unfortunately, there was subsequent significant graft loss on the back proving to be a stubborn area to treat despite further grafting sessions. This challenge led to the decision to use Vivostat ® (Vivostat A/S, Lillerød, Denmark) and Recell ® to resurface the back. Results: The patient underwent one session of resurfacing with Vivostat ® (Vivostat A/S, Lillerød, Denmark) and Recell ® and went on to have full healing on the back. Conclusions: NICE (The National Institute for Health and Care Excellence) states that Recell ® shows potential to improve healing in acute burns and we believe that its co-delivery with fibrin via Vivostat ® (Vivostat A/S, Lillerød, Denmark) allows for precise delivery of the fibrin suspended cells while minimising loss in the "run off" encountered when Recell ® is just simply sprayed on, assisting the anchoring of keratinocytes to the wound surface and thus aiding in the treatment of challenging areas.